The Importance of Mealybugs and Colony Compatibility in Augmentation of Dolichoderus Thoracicus (Smith) (Hymenoptera: Formicidae) Populations in Cocoa - Ho, Cheng Tuck (1991)

(untitled)
In the artificial introduction of the black cocoa ant Dolichoderus thoracicus (Smith) for cont rolling mirid damage in cocoa in Malaysia, initial establishment of introduced ants were often good but the effect was frequently not sustained. This under scored the need for augmentation of populations of both the ant and its mutualistic mealybug Cataenococcus hispidus (Morrison). Honeydew of C. hispidus was demonstrated to be the main and preferred source of food of Q. thoracicus. This emphasises the need for mealybug establishment prior to ant introduction for success in establishment of the latter. Transport of C. hispidus by Q. thoracicus was established. Transport was the cumulative effect of random occasions of nymphs being carried in the mandibles of worker ants in the general direction of the ant's trails. Di rect spread of C. hispidus was effected by crawlers. Crawlers were most stimulated to do this when mother colonies were stressed, particularly through the dessication of host substrate.